2021
DOI: 10.1371/journal.pmed.1003828
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of type 2 diabetes remission in Scotland in 2019: A cross-sectional population-based study

Abstract: Background Clinical pathways are changing to incorporate support and appropriate follow-up for people to achieve remission of type 2 diabetes, but there is limited understanding of the prevalence of remission in current practice or patient characteristics associated with remission. Methods and findings We carried out a cross-sectional study estimating the prevalence of remission of type 2 diabetes in all adults in Scotland aged ≥30 years diagnosed with type 2 diabetes and alive on December 31, 2019. Remissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
4
16
0
1
Order By: Relevance
“…However, how common the remission of T2D was among the general population remained poorly reported. A cohort investigation from Scotland estimated 4.8% of the prevalence of T2D remission in 2019 among 162 316 national T2D register 18 . The study further summarized that participants in remission tended to be older, have a lower HbA1c at diagnosis, with no history of antidiabetic prescription, succeed in any weight loss from diagnosis, and have had previous history of bariatric surgery, comparing to participants who did not achieve remission, which were coincided with experience from previous intervention studies 19,20 .…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…However, how common the remission of T2D was among the general population remained poorly reported. A cohort investigation from Scotland estimated 4.8% of the prevalence of T2D remission in 2019 among 162 316 national T2D register 18 . The study further summarized that participants in remission tended to be older, have a lower HbA1c at diagnosis, with no history of antidiabetic prescription, succeed in any weight loss from diagnosis, and have had previous history of bariatric surgery, comparing to participants who did not achieve remission, which were coincided with experience from previous intervention studies 19,20 .…”
Section: Discussionsupporting
confidence: 63%
“…A cohort investigation from Scotland estimated 4.8% of the prevalence of T2D remission in 2019 among 162 316 national T2D register. 18 The study further summarized that participants in remission tended to be older, have a lower HbA1c at diagnosis, with no history of antidiabetic prescription, succeed in any weight loss from diagnosis, and have had previous history of bariatric surgery, comparing to participants who did not achieve remission, which were coincided with experience from previous intervention studies. 19,20 Therefore, ascertainment of those characteristics contributed to the identification of individuals with T2D who were most likely to achieve and maintain remission, which was important for making informed decisions regarding relevant T2D management and intervention.…”
Section: Discussionmentioning
confidence: 64%
“…Partial studies have shown that weight loss could induce T2DM remission in a dose-dependent manner ( 9 , 10 , 18 , 19 ). However, in our study, the body weight changes during VLCR did not differ significantly between the two groups, which is consistent with the results from DiRECT sub-study ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The long-term remission rate of T2DM after VLCR has been investigated. A cross-sectional study from Scotland in 2019 reported that 4.8% of patients with T2DM achieved remission, manifested as HbA1c < 6.5% in the absence of glucose-lowering therapy for at least 12 months ( 9 ). A 2-year remission rate of 35.6% after VLCR was achieved in the Diabetes Remission Clinical Trial (DiRECT), which performed the longest follow-up for analyzing T2DM remission ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…This improvement in glucose levels back to a normal or near-normal interval can be achieved by lifestyle changes or following a number of interventions [13,14]. A recent observational study in 162,316 T2D subjects reports that remission occurred in 5% of cases, and that factors associated with remission were older age, HbA1c < 48 mmol/mol (6.5%) at diabetes diagnosis, no previous history of glucoselowering therapy, weight loss and bariatric surgery [15]. [13,14]).…”
Section: Introductionmentioning
confidence: 99%